Fatherlessness and Psychological Well-Being: Examining the Relationship Among Adolescent - Tiara Natasya Apriliyanti Apriliyanti; Rosada Rosada; Yuda Syahputra; Farouq Fathurrahman (Asosiasi Asesmen Pendidikan (AAP), 2026)
The phenomenon of fatherlessness has become an issue that is receiving increasing attention due to its potential to affect adolescents’ psychological development, including their psychological well-being. This study aims to examine the relationship between fatherlessness and psychological well-being among adolescents. This study employs a quantitative, correlational design. The sampling technique used was purposive sampling. The criteria used were adolescents aged 15–18 years who were raised without a father and were willing to participate in the study, resulting in a sample size of 202 adolescents. Data collection was conducted using the Fatherless Scale and the Psychological Well-Being Scale, which were distributed via Google Forms. Data analysis was performed using the Pearson Product-Moment correlation technique with the aid of IBM SPSS Statistics. The results of the study indicate that there is a significant relationship between fatherlessness and psychological well-being among adolescents, with a significance value of 0.000 (p < 0.05) and a correlation coefficient of -0.460. The results indicate a negative correlation of moderate strength, meaning that the higher the level of fatherlessness experienced by an individual, the lower their level of psychological well-being. Conversely, the lower the level of fatherlessness, the better the individual’s psychological well-being tends to be. These findings suggest that a father’s involvement plays an important role in supporting adolescents’ psychological well-being.